Teacher's Readiness to Implement Digital Assessment Activities - Vy, Nguyen Thi Phuong; Hung, Le Thai; Hoai, Nguyen Thi; Yen, Nguyen Hoang (VNU Journal of Science: Education Research; Vol 39 No 1DO - 10.25073/2588-1159/vnuer.4662, 2022)
The Covid 19 pandemic strongly impacted every aspect of life, including education. With technology support, Courses gradually shift to online or blended learning forms, including teaching and assessment activities. The current situation creates challenges for teachers and pedagogical students. Using the systematic review method, the article proposes a framework to evaluate the readiness of teachers to perform assessment activities in the digital context. Four factors are mentioned, including: i) Understanding of digital assessment; ii) Confidence in performing digital assessment skills; iii) Feeling in the digital assessment experience; and iv) Belief in the effectiveness of the digital assessment. Research on the components of digital assessment readiness contributes a basis for further studies on developing the tools to assess the readiness to use the digital assessment platforms for teachers and pedagogical students.